The sweater workshop : knit creative, seam-free sweaters on your own with any yarn - Fee, Jacqueline (Camden, ME : Down East Books, 2002)
Fee works through a sweater sampler that includes every technique needed to master knitting seamless sweaters in the round, then moves on to a basic sweater.
Includes bibliographical references and index.
Keywords: Knitting; Sweaters